Tokoh Teologi Islam Kontemporer : H.M Rasjidi - Nuraeni Nuraeni (LP2M IAI Muhammadiyah Sinjai, 2020)
In the history of Islamic thought from century to century, more and more figures of Islamic thought have emerged from all over the world. Especially from Indonesia itself also has figures of Islamic thought, one of which is H.M Rasjidi, who is very well known among Indonesian Islamic thought leaders. In this paper, we will discuss the biography and some topics of HM's thoughts. Rasjidi during his life. In this paper, we examine the Library Research method from the literature presented by the author later